1987
DOI: 10.1073/pnas.84.21.7730
|View full text |Cite
|
Sign up to set email alerts
|

Tubulofilaments in negatively stained scrapie-infected brains: relationship to scrapie-associated fibrils.

Abstract: A simple method was devised for negativestain transmission electron microscopy of brain infected with the agent of scrapie. Brains of infected' hamsters contained large masses of tubuloframentous structures with irregular fuzzy surfaces. Brains of mice infected with Creutzfeldt-Jakob disease agent contained similar tubulofilaments in smaller numbers. The abnormal tubulofilaments resembled but were distinguished from normal microtubules. On grids soaked in sodium dodecyl sulfate the abnormal tubuloframents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
4
26
1
Order By: Relevance
“…The grids prepared by the impression method were treated with several different proteases and nucleases. This study confirms the previous observations [9,15] that the tubulofilamen tous particle contains a central core with a single-stranded DN A (ssDNA) which is pro tected by a protein coat of unknown origin.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…The grids prepared by the impression method were treated with several different proteases and nucleases. This study confirms the previous observations [9,15] that the tubulofilamen tous particle contains a central core with a single-stranded DN A (ssDNA) which is pro tected by a protein coat of unknown origin.…”
Section: Introductionsupporting
confidence: 81%
“…Recently, experi ments have shown that SAF/PrP can be de tected in brains of infected mice and ham sters, but not in their spleen samples with a similar titre of infectivity [10], Infectivity also has been demonstrated in the absence of prion rods [11] and can be separated from any identifiable structure [12], In addition to SAF, one other type of structure, tubulofilamentous particle, is seen in a thin section by electron microscopy in all spongiform encephalopathies -experimen tal and natural [13,14]. Using scrapie-infected hamster brains, negative staining of grids prepared by an 'impression' technique de monstrated that SAF form the core of tubulofilamentous particles [9,15]. The present study was extended to mice infected with four different strains of scrapie.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 263K strain of scrapie agent (9) was used at the fourth passage level as described (1 units/ml diluted in buffer recommended by the supplier; and (ix) diluent alone. Grids were immersed under 0.5 ml of solution and incubated in a moist chamber.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, after a 30-min treatment with proteinase K, collagenase, or trypsin, grids were washed and then treated with 2% NaDod-S04 or stained with 0.02% aqueous ethidium bromide (Calbiochem) by floating on a drop for 5 min; grids were then washed five times with distilled water, fixed, and stained as above. After incubations of 30, 60, 90, or 120 min, 2 grids were removed from each group, washed three times with 0.1 M MgCl2 and three times with distilled water, and then fixed with ruthenium red, glutaraldehyde, and osmium tetroxide as described (1). Finally grids were stained with phosphotungstic acid (pH 6.6) for 30 sec, edge-drained on filter paper, and air-dried.…”
mentioning
confidence: 99%